2019
DOI: 10.1103/physrevb.99.195413
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance in defect spins mediated by spin waves

Abstract: In search of two level quantum systems that implement a qubit, the nitrogen-vacancy (NV) center in diamond has been intensively studied for years. Despite favorable properties such as remarkable defect spin coherence times, the addressability of NV centers raises some technical issues. The coupling of a single NV center to an external driving field is limited to short distances, since an efficient coupling requires the NV to be separated by only a few microns away from the source. As a way to overcome this pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…At the off-resonant condition, /√ follows an average value of 120 MHz/√mW. The enhancement ratio of /√ reaches 129, 138, 48, and 17 at the resonant condition of k1, k2, k3, and k4 spin wave modes, respectively, in quantitative agreement with the analytical theoretical calculations 35 (see supplementary note 2). We notice that the enhancement of /√ decreases with the increase of the wavevector, which is attributable to a reduced microwave excitation efficiency of the higher order propagating spin wave modes.…”
Section: (B) a Diamondsupporting
confidence: 82%
“…At the off-resonant condition, /√ follows an average value of 120 MHz/√mW. The enhancement ratio of /√ reaches 129, 138, 48, and 17 at the resonant condition of k1, k2, k3, and k4 spin wave modes, respectively, in quantitative agreement with the analytical theoretical calculations 35 (see supplementary note 2). We notice that the enhancement of /√ decreases with the increase of the wavevector, which is attributable to a reduced microwave excitation efficiency of the higher order propagating spin wave modes.…”
Section: (B) a Diamondsupporting
confidence: 82%
“…10(e)], it was demonstrated that directly driving these spin waves could coherently drive NV centers over a distance of several hundred microns up to several millimeters,. 209,210,251 In particular, it was found that reducing the microwave power reduced noise from off-resonant spin wave excitations and revealed a considerable enhancement of the local microwave driving field mediated by spin waves compared to the driving field directly coupled to the antenna. As observed in Fig.…”
Section: Magnonic Systems For Quantum Interconnectsmentioning
confidence: 99%
“…2c, a discretized and broadened resonance line owing to the frequency matching between the NV spins and the different MSSW modes (Fig. 2d) was observed 17,34 (Fig. 2e).…”
Section: System and Experimental Proceduresmentioning
confidence: 90%